1998
DOI: 10.1037/1040-3590.10.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Five validation experiments of the Test of Memory Malingering (TOMM).

Abstract: Malingering (TOMM; T. N. Tombaugh, 1996) is a newly developed visual recognition test that uses pictures of common objects as stimuli. Prior normative research with community-dwelling adults and neurologically impaired patients has shown that the TOMM possesses a high degree of specificity and is not affected by demographic variables such as age and education. The current series of 5 integrated experiments was designed to provide important validation data. Converging evidence from all studies showed that score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
0
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(113 citation statements)
references
References 40 publications
9
95
0
8
Order By: Relevance
“…As such, values, interpretation, and discussion of the CVLT-II FCR and CIA indices is qualified and limited by the gold standard measures to which they are compared. With regard to sensitivity and specificity values for the TOMM, previous studies indicate sensitivity rates ranging between 77% and 100% in simulation studies of malingering, with corresponding specificity rates all at 100% (Rees et al, 1998;Tombaugh, 1996Tombaugh, , 1997. With regard to sensitivity and specificity of the VIP, the original validation study indicates sensitivity rates of the Verbal subtest at 67%, the Nonverbal subtest at 74%, either subtest at 78%, and both subtests at 63%; corresponding specificity rates were 83% for the VIP Verbal subtest, 86% for the Nonverbal subtest, 78% for either subtest, and 93% for both subtests (Frederick, 1997).…”
Section: Detection Of Inadequate Effort On the Cvlt-iimentioning
confidence: 99%
See 1 more Smart Citation
“…As such, values, interpretation, and discussion of the CVLT-II FCR and CIA indices is qualified and limited by the gold standard measures to which they are compared. With regard to sensitivity and specificity values for the TOMM, previous studies indicate sensitivity rates ranging between 77% and 100% in simulation studies of malingering, with corresponding specificity rates all at 100% (Rees et al, 1998;Tombaugh, 1996Tombaugh, , 1997. With regard to sensitivity and specificity of the VIP, the original validation study indicates sensitivity rates of the Verbal subtest at 67%, the Nonverbal subtest at 74%, either subtest at 78%, and both subtests at 63%; corresponding specificity rates were 83% for the VIP Verbal subtest, 86% for the Nonverbal subtest, 78% for either subtest, and 93% for both subtests (Frederick, 1997).…”
Section: Detection Of Inadequate Effort On the Cvlt-iimentioning
confidence: 99%
“…As discussed previously, any comparison between a gold standard measure and a candidate measure will be limited by the ultimate sensitivity and specificity values of the gold standard. Although both the TOMM and VIP have acceptable sensitivity and specificity values, a subset of individuals exhibiting inadequate effort are missed by both measures in previous studies (Frederick, 1997;Rees et al, 1998;Tombaugh, 1996Tombaugh, , 1997. Other measures, such as the Word Memory Test (Green et al, 1996), may offer increased agreement with the FCR and CIA, due to reported higher sensitivity rates (Gervais et al, 2004).…”
mentioning
confidence: 90%
“…Using a criterion cutoff score of 45 on Trial 2, TOMM had specificity rates of greater than 90% (Rees, Tombaugh, Gansler, & Moczynski, 1998;Tombaugh, 1996) a,c…”
Section: General Description Reliability Data Validity Datamentioning
confidence: 99%
“…In general, the neurocognitive literature explains that the features of the TOMM are insensitive to the effects of neurocognitive impairment (Tombaugh, 1997). There is also evidence for the specificity of the TOMM for individuals who have sustained traumatic brain injuries, in which the effects of the injury did not increase false positive results (Rees et al, 1998). Despite the TOMM's insensitivity to the effects of neurocognitive impairment, there is evidence to caution clinicians to rule out dementia diagnoses in order to prevent misclassification of malingering (Teichner & Wagner, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although the retention trial, a delayed, non-forced choice memory task, has been reported to be optional (Tombaugh & Tombaugh, 1996), research has indicated that, unless a comparable symptom validity test is also administered in the battery, the retention trial must be administered for greater accuracy (Greve & Bianchini, 2006). Examination of the instrument has demonstrated that a criterion cutoff score of 45 on Trial 2 provided 95% accuracy of identifying non-malingering patients without dementia, and specificity of 91% with all patients (Rees, Tombaugh, Gansler, & Moczynski, 1998;Tombaugh, 1997;Tombaugh & Tombaugh, 1996).…”
Section: Introductionmentioning
confidence: 99%